CRITERIA FOR ASSESSING CORPORATE DEVELOPMENT RISKS ARISING WITH INTRODUCTION OF FINANCIAL TECHNOLOGIES - E. A. Demyanova (Финансы: теория и практика, 2017)
The introduction of financial technologies has a significant impact on the development of companies in all sectors of the economy. The financial gurus of the Russian Federation and world experts agree that the financial institutions of all countries will undergo radical changes in the coming years. Companies, regardless of their size, form of ownership and type of business, are being brought into the orbit of new financial technologies; the ways of doing business are also changing. The government program of 2017–2025 “The Digital Economy” is becoming a new benchmark and a kind of compass in the world of money circulation. The introduction of financial technologies gives rise to new risks not previously considered. The paper provides examples of principally new approaches to risk assessment and emphasizes the increasing importance of using large amounts of data. The author examines the scope of new uncovered risks of corporate development, defines concepts and systematizes such risks at macro and micro levels along with their comparison. The study compares risk assessment approaches of reputed international expert organizations, such as the World Economic Forum, COSO ERM, leading international consulting companies and the Bank of Russia. Authors of previously published works only listed new risks without developing particular criteria for their assessment, though emphasizing the big practical potential of the latter. Based on the analysis of characteristics of non-covered corporate development risks arising with introduction of financial technologies, the author offers her own approach to classification of assessment criteria and a version of the working classification of criteria for assessing two of the most important non-covered corporate development risks: the cyber-crime security risk and the IoT risk. The assessment criteria are understood as a verbal description of risk consequences and a “qualitative” assessment of probabilities without conversion to quantitative indicators. Experts can use this classification in practice with further risk rating on the basis of expert risk assessment.